DEMAND MASYARAKAT KECAMATAN SUKORAMBI TERHADAP PELAYANAN KESEHATAN PUSKESMAS SUKORAMBI DI KABUPATEN JEMBER - Nurjana, Nurjana; Nuryadi, Nuryadi; Anjarsari, Alice (IKESMA, 2008)
The demand of residents of Sukorambi sub-district for health care of Public Health Center (Puskesmas) at the sub-district decreased by 0.82% on 2007, and the target of 50% public visit could not be fulfilled. The objective of this research is to analyze the demand of residents of Sukorambi sub-district for health care that are provided by the Puskemas of Sukorambi sub-district in relation with the sub-districtâs characteristics of demography, residentsâ trust in health care, frequency of disease infection, residentsâ level of knowledge as well as residentsâ level of income. This study uses a descriptive method of survey of which the sample-taking procedure is by means of proportional allocation and simple random sampling technique. The results of research indicate that the percentage of residents of Sukorambi sub-district who had the demand for health care of the Puskesmas was 59.05%, whereas the residents who did not have the demand for health care of the Puskesmas wasÂ  40.95%. The majority of residents of Sukorambi sub-district who had the demand for health care of the Puskesmas was female, that was 53.51%, of which the highest percentage was elderly residentsâthat was 53.89%, had trust in the medical servicesâthat reached 89.62%, had less frequency of disease infectionâthat was 54.72%, had a high level of knowledgeâthat was 72.69%, and had a relatively low incomeâthat reached 53.77%. Â  Keywords: demand, residents, health care